Analisis Kualitas Pelayanan Perpustakaan Berbasis LibQUAL untuk Mengukur Kepuasan Pengunjung dengan Metode Exploratory Factor Analysis (EFA): Studi Kasus Perpustakaan Kota Jakarta - Muhammad Dimas Sudirman; Nadia Mumtaz Prasetyo; Michelle Kanto; Jakaria Jakaria (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to evaluate the service quality of the Jakarta City Library using an instrument adapted from the LibQUAL model to describe key service-quality dimensions related to visitor satisfaction. The research applies a quantitative approach by collecting data through questionnaires distributed to library users. Data analysis includes tests of sampling adequacy and correlation suitability using the Kaiser–Meyer–Olkin (KMO) measure and Bartlett’s Test of Sphericity, reliability testing, and exploratory factor analysis using Exploratory Factor Analysis (EFA) with Principal Component Analysis (PCA) extraction and Varimax rotation. The findings indicate that the data are highly suitable for factor analysis. The instrument also demonstrates strong reliability, and all indicators meet validity and internal consistency criteria for measuring the intended construct. Based on the EFA results, two main factors emerge and explain the data structure satisfactorily. The first factor is interpreted as Service Quality and Information Access, encompassing empathy, responsiveness, assurance, reliability, ease of access, independent information seeking, and the support of information technology facilities. The second factor is interpreted as Library Comfort and Physical Environment, reflecting the availability and adequacy of collections, the condition of physical facilities, and a learning-friendly atmosphere that supports user activities. These results suggest that the identified factor structure has a strong empirical basis and can serve as a reference for formulating strategies to improve service quality and enhance the library environment in order to maintain visitor satisfaction and loyalty.